Uji Pemanfaatan Teknologi Elektroplating Pada Produk Pandai Besi Sebagai Upaya Peningkatan Kualitas dan Daya Saing - Mubin, Ahmad (Jurnal Teknik Industri, 2001)
The research of application of electroplating technology testing at pandai Besi product as means to increase of quality and competitiveness had done, this research aimed to make reparation of production process and to applied electroplating technology in finishing process, until can adding to decorative properties and resistence of corrosion at product and to determine cost addition because that treatment.